Indigenous ecological wisdom as civic virtue: The Tiaytiki practice in Papua, Indonesia - Yakob Godlif Malatuny; Hermina Nelci Yaroseray (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This research explores the local wisdom of Tiaytiki of the Yepase community in Jayapura Regency, Papua, as a form of citizen virtue in caring for and maintaining the sustainability of marine ecology. The ancestors have passed Tiaytiki down to the current community, which serves to preserve marine resources through zoning mechanisms, prohibitions on overexploitation, and the application of customary sanctions. Rooted in local beliefs and cosmology, Tiaytiki is not only a technical customary rule but also a substantial moral expression that emphasises collective responsibility, social solidarity, and spiritual awareness to live in harmony with nature. The research has been conducted qualitatively using the case study method. Research data were collected through in-depth interviews, participatory observation, and documentation. The analysis shows that there are five dimensions of civic virtue in Tiaytiki: spiritual, social, educational, marine-ecological, and institutional, which can serve as a model for caring for nature. This model not only serves as a mechanism for marine conservation but also as an educational tool to instil ecological character in the younger generation. The findings confirm that Tiaytiki is the intersection of civic ecology and civic virtue, and that it contributes to the development of contextualised civic education oriented towards environmental sustainability.